Penerapan Metode Kibar dalam Meningkatkan Kemampuan Membaca Al-Qur’an di Kelas VI SD Negeri 82 Palembang - Syarifah; Syarnubi, Syarnubi; Zulhijra, Zulhijra; Firdaus, Aristophan; Padli, Padli; Sukardi, Ismail (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
This research discusses the application of the Kibar method in improving the ability to read the Al-Qur'an in Class VI of SD Negeri 82 Palembang. The aim is to determine the application of the Kibar method in improving students' ability to read the Al-Qur'an. This research aims to find out whether there is an increase in students' ability to read the Al-Qur'an before and after the Kibar method is applied. This research is quantitative research which aims to determine the influence, namely causes and impacts, where in this research the analysis is carried out using numbers so that it gets a more accurate meaning compared to using words. The type of research used is One Group Pretest-Posttest Design experimental research. The sample for this research was 30 class VI students. The data collection method uses observation, tests and documentation, while the data analysis technique uses the t test formula. The results of this research show that 1) Students' ability to read the Al-Qur'an before implementing the Kibar method was 6 students in the high category, 19 students in the medium category, and 5 students in the low category. 2) Students' ability to read the Koran after applying the Kibar method was 9 students in the high category, 17 students in the medium category, and 4 students in the low category. 3) Based on the paired samples t-test table, the significance value obtained is 0.001, which means less than 0.05 and the calculated t value of 17,906 is greater than the t table, namely 1.699, indicating that there is a significant difference between the pretest and posttest, this shows that there is differences in treatment for each variable. From the calculations above, it can be concluded that H0 is rejected, meaning that there is an increase in the application of the Kibar method in improving the ability to read the Al-Qur'an in class VI of SD Negeri 82 Palembang.